Efektivitas Penggunaan Modul Pembelajaran Kimia Berbasis POE Materi Larutan Elektrolit dan Non Elektrolit terhadap Hasil Belajar - Mutia Lela; Amilda Amilda; Etrie Jayanti (Chemistry Education Department of Education and Teaching Faculty, 2023)
This study is motivated by problems related to low student learning outcomes caused by the use of learning resources that are still ineffective and the learning process is still focused on the teacher as the main learning resource. This study aimed to determine the effectiveness of a POE (predict, observe, explain) based chemistry learning module in electrolyte and non-electrolyte solution material on students’ learning outcomes. This was experimental research in the form of pre-experimental with a one-group pretest-posttest design model. The sample in this study was students of class X IPA at one of the public high schools in the Ogan Komering Ilir District, and the sampling in this study used a simple random sampling technique. The data collection technique used in this study was in the form of tests where the instruments were pre-test and post-test questions in the form of multiple choice questions. The effectiveness of the module is seen from the results of data analysis of student learning outcomes using n-gain score and t-test data analysis. Based on the analysis of the n-gain score data, an average score of 0,58 was obtained which was included in the medium category, and the hypothesis test results obtained a sig (ρ) value of 0,000 ˂ 0,05, which means H0 is rejected and H1 is accepted. Based on the analysis results, it was concluded that POE (predict, observe, explain) based chemistry learning module is effective for students’ learning outcomes and can be used as an alternative teaching material.